A methodology for brand feature establishment based on the decomposition and reconstruction of a feature curve. (October 2018) - Hsiao, Shih-Wen; Lee, Chu-Hsuan; Chen, Rong-Qi; Lin, Chien-Yu
Highlights: A feature curve decomposition-reconstruction method for product design is proposed. In this way the brand feature of a product can be recognized and reserved. The brand feature can be redesigned in a parametric way. The 2D feature can be extended to 3D form by shape morphing and blending. A residual modified grey prediction method for new form development is addressed. Abstract: For creative products, maintaining original brand elements and features in a new product is an important issue in the design process as brand features are conceived and generated for longevity. However, current methods rely on designers' abilities, and the size of forms is easily affected when shape morphing is applied, causing limitations in computer-aided design. In order to focus on design while preserving key features, a systematic method for presenting brand features is proposed in this article. In this method, the feature curves of the brand features of a company are decomposed with defined feature parameters, which were then used to reconstruct the feature curve of the designed product in the design stage by using a residual modified gray prediction model. A classic vehicle configuration design is taken as an example to show the implementation procedure of the proposed method. With residual modification, this method can also assimilate other forms from the original form database, and generate new forms based on gray prediction. The results show that brand features can be retained in the newly designed product based on the proposed method. Though vehicle design is taken as the example, this method can also be used to develop designs for many other the brand features. For classic products with historical value, this method can generate new forms that maintain original brand features, thereby satisfying customers' needs for brand authenticity.